1996
DOI: 10.1002/(sici)1096-8628(19960503)63:1<268::aid-ajmg45>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Serial examination of 20,248 newborn fetuses and infants: Correlations between drug exposure and major malformations

Abstract: Maternal medication during the first trimester of pregnancy has been discussed as a risk factor for development of birth defects. The correlation between maternal drug use and major malformations was investigated in a population‐based case‐control study in Mainz. Over a period of 5 years (1990–1994), 20,248 livebirths, stillbirths, and abortions underwent physical and sonographic examination, and anamnestic data were collected. A total of 1,472 births with congenital anomalies (cases) and 9,682 births without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…To our knowledge there have been no previous studies that have sought a possible association between over‐use of thyroid hormones and malformations. Use of levothyroxine during pregnancy has been associated with a slightly higher risk of malformations . Also, even though most recommendations aim to facilitate the benefits of treatment with levothyroxine in pregnant women with hypothyroidism, several studies have shown that women are reluctant to use any medications during pregnancy, even those that are probably harmless and potentially necessary .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge there have been no previous studies that have sought a possible association between over‐use of thyroid hormones and malformations. Use of levothyroxine during pregnancy has been associated with a slightly higher risk of malformations . Also, even though most recommendations aim to facilitate the benefits of treatment with levothyroxine in pregnant women with hypothyroidism, several studies have shown that women are reluctant to use any medications during pregnancy, even those that are probably harmless and potentially necessary .…”
Section: Discussionmentioning
confidence: 99%
“…One large prospective study (Heinonen et al, 1977) and two large retrospective studies (Khoury et al, 1989; Queisser‐Luft et al, 1996) examined maternal thyroid disease or thyroid medication use and a variety of birth defects. All three studies reported positive associations between hyperthyroidism (Heinonen et al, 1977; Khoury et al, 1989) or thyroid hormone use (Queisser‐Luft et al, 1996) and central nervous system defects overall with ORs ranging from 2.0 to 4.1. Khoury et al (1989) noted increased ORs for hyperthyroidism and specific central nervous system defects, encephalocele, and hydrocephaly, with ORs of 5.26 (95% CI, 1.16–24.0) and 3.05 (95% CI, 1.23–7.59), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The NBDPS does not have a category for “intestinal malrotation” for comparison with the positive results from Khoury et al Our OR for thyroid disease and isolated longitudinal limb deficiencies (OR, 2.1, 95% CI, 0.8–5.2), though not significant, was similar to the estimate by Khoury et al for hypothyroidism and all limb deficiencies (OR, 1.92; 95%CI, 1.04–3.54). Queisser‐Luft et al (1996) noted an OR of 3.9 (95% CI, 1.9–8.0) for first‐trimester thyroxine use and “external genitourinary defects,” the majority of which were hypospadias (personal communication, A. Queisser‐Luft 2008). We observed an OR of 1.7 (1.0‐2.7) for periconceptional thyroxine use and hypospadias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A teratogenic effect of treatment with thyroid hormone is unlikely, because it is the same as thyroid hormone that is produced endogenously. Yet, some animal studies suggest that thyroid hormone supplements may be teratogenic (Giroud et al, ; Miyamoto, ; Lavado‐Autric et al, ), and epidemiologic studies have mixed results (Heinonen, ; Queisser‐Luft et al, ; Wikner et al, ; Browne et al, ; Samadi et al, ). Accumulating evidence suggests anti‐thyroid medications may have teratogenic effects, with MMI associated with more severe birth defects (Browne et al, ; Clementi et al, ; Bowman and Vaidya, ; Yoshihara et al, ; Andersen et al, , ; Andersen and Laurberg, ; Laurberg and Andersen, , ).…”
Section: Introductionmentioning
confidence: 99%